Greater general startle reflex is associated with greater anxiety levels: a correlational study on 111 young women - Poli, Eleonora; Angrilli, Alessandro (Frontiers in Behavioral Neuroscience, 2015)
Startle eyeblink reflex is a valid non-invasive tool for studying attention, emotion and psychiatric disorders. In the absence of any experimental manipulation, the general (or baseline) startle reflex shows a high inter-individual variability, which is often considered task-irrelevant and therefore normalized across participants. Unlike the above view, we hypothesized that greater general startle magnitude is related to participants’ higher anxiety level. 111 healthy young women, after completing the State-Trait Anxiety Inventory, were randomly administered 10 acoustic white noise probes (50 ms, 100 dBA acoustic level) while integrated EMG from left and right orbicularis oculi was recorded. Results showed that participants with greater state anxiety levels exhibited larger startle reflex magnitude from the left eye (r109=0.23, p<0.05). Furthermore, individuals who perceived the acoustic probe as more aversive reported the largest anxiety scores (r109=0.28, p<0.05) and had the largest eyeblinks, especially in the left eye (r109 = 0.34, p<0.001). Results suggest that general startle may represent a valid tool for studying the neural excitability underlying anxiety and emotional dysfunction in neurological and mental disorders.